Holomorphic anomaly equations and the Igusa cusp form conjecture - Oberdieck, Georg; Pixton, Aaron C. (Inventiones mathematicae, 2018)
Let S be a K3 surface and let E be an elliptic curve. We solve the reduced Gromov-Witten theory of the Calabi-Yau threefold